Alcohol Price Floors and Externalities: The Case of Fatal Road Crashes. (13th October 2022) - Francesconi, Marco; James, Jonathan
Abstract: In May 2018, Scotland introduced a minimum unit price on alcohol. We examine the impact of this policy on traffic fatalities and drunk driving accidents. Using administrative data on the universe of vehicle collisions in Britain and a range of quasi‐experimental modeling approaches, we do not find that the policy had an effect on road crash deaths and drunk driving collisions. The results are robust to several sensitivity exercises. There is no evidence of effect heterogeneity by income and other predictors of alcohol consumption or cross‐border effects. A brief discussion of the policy implications of our findings is provided.